Availability of 'Do-It-Yourself' orthodontics in the United Kingdom. (March 2022) - Carter, Annabelle; Stokes, Susan
Objective: To identify the number of companies providing Do-It-Yourself (DIY) orthodontics and explore information available on websites for DIY brace providers operating in the UK. Design: Web search and review of websites providing DIY braces. Setting: Leeds, UK. Methods: A Web search was completed in November 2020 and April 2021 of all companies providing DIY braces for UK consumers. Each website was evaluated, and the following data collected: name; year started operating; costs; process; involvement of a dental professional; average 'treatment' length; retention; consent process; information on risks and benefits; aligner material; social media presence; age suitability; and consumer ratings on Trustpilot. Quality of website information was assessed via the DISCERN tool. Results: Seven DIY orthodontic companies were operating in the UK. Websites reviewed revealed the following: product costs were in the range of £799–£1599, 'treatment' length quotes were in the range of 4–12 months; Trustpilot reviews were in the range of 1.6–4.8 stars; and websites claimed their aligners were suitable for individuals with an age range of 12–18 years. Quality of content regarding risks described on websites varied, and there was limited information regarding involvement of a dental professional. Quality of websites information scored 'poor' or 'very poor' on the DISCERN scoring. Conclusions: There has been an increase in the number of DIY orthodontic companies operating in the UK over the last three years. There is a need to determine whether these products constitute dental treatment in their own right. If so, it is crucial to ensure these are regulated appropriately with adequate information available to satisfy informed consent and have greater transparency over dental professional involvement to safeguard the public.